Whose Story Is It? Media Portrayals of Children in Conflict and Migration Contexts - Onyejelem, Timothy Ekeledirichukwu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
This paper examines media portrayals of children in contexts of conflict and migration, interrogating the narratives, visual representations, and framing strategies employed in both global and local media. Using secondary data, the paper explores how children are often depicted as passive victims, security threats, or symbols of hope, rather than as agents with voices and rights. It investigates whose perspectives dominate the storytelling, whether those of journalists, governments, aid agencies, or the children themselves, and the implications of such representations for public perception, humanitarian response, and policy advocacy. The paper calls for more inclusive, context-sensitive, and child-centred reporting frameworks that recognize children not merely as subjects of pity or fear, but as individuals with agency, resilience, and stories worth telling on their own terms. This paper has shown that mainstream media often depict children through reductive frames, either as passive victims or as security threats, thus stripping them of agency and voice. These portrayals are frequently influenced by geopolitical interests, cultural biases, and editorial agendas that prioritize sensationalism over complexity. While some media efforts attempt to humanize children and highlight their resilience, structural limitations and editorial conventions often impede more balanced storytelling. A child-rights-based and ethical media framework is therefore essential to ensure that children's experiences are accurately and respectfully represented.